Wideband bandstop frequency selective structures - Ali Al-Sheikh (2015)
Frequency selective surfaces brought several design challenges to light, and have been central to much research recently. Known limitations are: poor filtering characteristics; sensitivity to large oblique incident angles when used as both filters and polarization manipulators, which results in a shift frequency response and deteriorated in- and out-of-band transmission and reflection responses; and the inability to maintain a satisfactory angular performance over a very wide bandwidth. This thesis introduces three novel designs based on a new class of three-dimensional frequency selective structure to present promising wideband bandstop structures suitable for different applications, following simple design procedures.